Exploring the Use of Ionic Liquid Mixtures to Enhance the Performance of Dicationic Ionic Liquids. Issue 8 (1st January 2017) - Lall-Ramnarine, Sharon I.; Suarez, Sophia N.; Fernandez, Eddie D.; Rodriguez, Chanele; Wei, Sujun; Gobet, Mallory; Jayakody, J. R. P.; Dhiman, Surajdevprakash B.; Wishart, James F.
Abstract : Dicationic ionic liquids (DILs) of diverse structural architectures (including symmetrical and asymmetrical ammonium, phosphonium and heterodications and the bis(trifluoromethylsulfonyl)amide (NTf2 − ) anion) have been prepared and used as additives to N -methyl- N -ethoxyethylpyrrolidinium (P1 EOE) NTf2, a relatively high-performing IL in terms of its transport properties (viscosity 53 mPa s). The three-ion, binary IL mixtures were characterized for their thermal and transport properties using differential scanning calorimetry, temperature dependent viscosity, conductivity and Pulsed Gradient Spin Echo (PGSE) NMR. Variable temperature 1 H, 19 F and 31 P self-diffusion coefficients were determined at 25, 60 and 75°C. The order of the diffusion coefficients was D(P1 EOE + ) > D(anion) > D(dication), and the composition of the dication had a strong effect on the degree to which diffusion of all three species is more or less coupled. IL mixtures containing about 30 mol % of the dicationic NTf2 and 70 mol % of P1 EOE NTf2 resulted in a significant decrease in glass transition temperatures and viscosities compared to the pure DIL. The mixtures extended the liquid range and potential for practical applications significantly. The data obtained here provides insight into the future design of dicationic salts tailored to exhibit lower viscosity and higher conductivities.